2008
DOI: 10.1111/j.1440-1746.2007.05052.x
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate attenuates experimental non‐alcoholic steatohepatitis induced by high fat diet

Abstract: EGCG reduces the development of experimental non-alcoholic steatohepatitis induced by a high fat diet. It seems to exercise this effect through its effect on lipid metabolism and antioxidant characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 39 publications
6
51
0
Order By: Relevance
“…Improvements in hepatic glutathione levels were accompanied by greater mRNA expression of glutamyl cysteine ligase, supporting the possibility that GTE may have activated the nuclear factor erythroid 2 (Nrf2) pathway, which regulates the transcription of genes related to the cellular antioxidant defense. Others have shown protection against NASH mediated by GTE or its catechins to be associated with decreased hepatic lipid peroxidation and increased plasma superoxide dismutase activity in the high-fat, choline-deficient model, 82 decreased hepatic lipid peroxidation and increased hepatic glutathione in the high-fat diet model, 102 and decreased oxidative DNA damage in the SREBP-1c overexpression model. 104 GTE may decrease oxidative stress either directly, by scavenging reactive oxygen and nitrogen species, or indirectly, by activating the Nrf2 pathway.…”
Section: Gte: Protective Effects Against the "Second Hit" Of Nashmentioning
confidence: 97%
See 1 more Smart Citation
“…Improvements in hepatic glutathione levels were accompanied by greater mRNA expression of glutamyl cysteine ligase, supporting the possibility that GTE may have activated the nuclear factor erythroid 2 (Nrf2) pathway, which regulates the transcription of genes related to the cellular antioxidant defense. Others have shown protection against NASH mediated by GTE or its catechins to be associated with decreased hepatic lipid peroxidation and increased plasma superoxide dismutase activity in the high-fat, choline-deficient model, 82 decreased hepatic lipid peroxidation and increased hepatic glutathione in the high-fat diet model, 102 and decreased oxidative DNA damage in the SREBP-1c overexpression model. 104 GTE may decrease oxidative stress either directly, by scavenging reactive oxygen and nitrogen species, or indirectly, by activating the Nrf2 pathway.…”
Section: Gte: Protective Effects Against the "Second Hit" Of Nashmentioning
confidence: 97%
“…102 The same dose of EGCG provided to mice overexpressing SREBP-1c for 12 weeks reduced histological evidence of hepatocyte ballooning and Mallory-Denk bodies. 104 EGCG protected against inflammation in these models but did not protect against fibrosis.…”
Section: Gte: Protective Effects Against the "Second Hit" Of Nashmentioning
confidence: 99%
“…A number of studies suggested that condensed tannins (proanthocyanidins) could improve metabolic syndrome such as dyslipidemia (Hsu & Yen, 2007;Liu et al, 2011), atherosclerosis (Zang et al, 2006), and non-alcoholic steatohepatitis (Kuzu et al, 2008). Our previous study showed that persimmon tannin could prevent hepatic steatosis in high-fat induced rats, and it was the main active component being responsible for the anti-hyperlipidemic effect of persimmon extract (Zou et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…C75 long-term treatment (30 days) decreased liver mass by 63% in ob/ob mice, although it was noted that treatment decreased food intake proportional to the observed decreases in liver mass [56]. In a model of steatosis in rats, EGCG was administered along with a high-fat diet for 6 weeks in rats, resulting in reduced alanine aminotransferase (marker of liver injury, ALT) levels, increased glutathione concentrations, and ultimately lower levels of steatosis [74]. EGCG was also shown to inhibit liver fibrogenesis after carbon tetrachloride treatment.…”
Section: Fas and The Treatment Of Fatty Liver Diseasementioning
confidence: 97%